THE EFFECT OF TRANSLANGUAGING PRACTICES ON SECONDARY SCHOOL STUDENTS’ FOREIGN LANGUAGE ANXIETY - Omanova, Aliya (Graduate School of Education, 2023)
Due to the historical background of Kazakhstan, the majority of the population is bilingual and used to mixing languages in their everyday life. However, it is not always welcomed by English as a Foreign Language teachers as they might be adherents of the monolingual approach in the classroom. As some research studies show, the monolingual approach may affect bilingual students' emotions, especially increase the level of Foreign Language Anxiety. This anxiety can be reduced through translanguaging. Therefore, this study aimed to explore the effect of translanguaging practices on secondary school students’ FLA level in Kazakhstan. Hence, this study applied a mixed method design in order to answer the two research questions: (1)What is Kazakhstani students' foreign language anxiety level in English language classes? (2) Do students with foreign language anxiety believe translanguaging reduces their anxiety? Firstly, 72 participants answered the Foreign Language Anxiety Classroom Scale and then 7 of them with a medium level of anxiety took participation in the semi-structured interviews. Next, the findings of the study were analyzed and interpreted with the help of two theoretical frameworks: (1) Horwitz et al’s. (1986) three aspects of FLA (communication apprehension, fear of negative evaluation, and test anxiety), and García et al’s. (2017) “translanguaging current”. The main findings of the study were that students had medium levels of anxiety and that they use translanguaging practices in usually anxiety-provoking situations and believe that it helps them. Thus, it is important to explore in further research studies those two phenomena from the perspective of students, in order to make their EFL studies more effective and less anxious.
Keywords: translanguaging; FLA; mother tongue; English language classroom